Optimization of Solid Waste Conversion Process and Risk Control of Groundwater Pollution - Xi, Beidou; Jiang, Yonghai; Li, Mingxiao; Yang, Yu.; Huang, Caihong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book focuses on the treatment and disposal technology used for solid waste in China, puts forward an optimal management scheme that takes into account the complete lifecycle, and introduces a new technical model that reflects the synergies of resource utilization and secondary pollution control. In addition, it provides a set of methods for professional on-site investigation, risk assessment, classification management and control to minimize the risk of groundwater contamination by solid waste at landfill. Given the extent and depth of knowledge and experience gathered in the book, it offers an important reference guide for government managers, environmental researchers, and all those involved in and concerned about solid waste disposal.
Introduction -- Cycle and transformation of solid waste and optimization management of multi-objective control -- Separated treatment and resuscitation of solid waste and its control of secondary pollution -- Treatment and disposal technology for hazardous waste -- Management situation of groundwater pollution of solid waste landfill -- Investigation and risk assessment of groundwater pollution of solid waste landfill -- Risk classification management of groundwater pollution of solid waste landfill.
Keywords: Environment; Environmental management; Waste management; Water pollution; Environment; Waste Management/Waste Technology; Environmental Management; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Electronic books